Chapter 2 Dutch literary translators' use and perceived usefulness of technology The role of awareness and attitude - Daems, Joke (Taylor & Francis, 2022)
Ch 2 - In this chapter, we report on a survey conducted among literary translators working from or into Dutch. A total of 155 literary translators filled out the survey. Questions cover translators' backgrounds and education, the types of technology they use (both general technology and technology specifically developed for translation), the types of translation technology they are aware of, and whether or not they feel these types of translation technology are (or can be) useful for literary translation. We verify whether date of birth, years of experience, and education have an impact on translators' use of translation technology. We use thematic analysis based on the Unified Theory of Acceptance and Use of Technology (UTAUT) to identify recurring topics and themes in respondents' answers to open questions, outlining the reasons why they feel technology is or is not useful for literary translation, what the main limitations of current technology are, and which components they feel the ideal literary translation tool should include.